Transgenerational Trauma and the Aboriginal Preschool Child: Healing through Intervention - Tracey, Norma (Rowman & Littlefield Publishers, 2014)
Transgenerational Trauma and the Aboriginal Preschool Child: Healing through Intervention approaches trauma from transgenerational perspectives that go back to the early colonization of Australia, and describes what that event has historically meant for the country’s Aboriginal population and its culture. This history has continued to propagate traumatically across subsequent generations. This book reveals the work underway at Gunawirra, a group in Sydney founded to work against transgenerational trauma in families with children aged 0–5. The group then began working with projects in more than forty country preschools throughout the state of New South Wales. Two intrinsic forms of healing that are an integral part of this ancient culture: Dadirri (deep listening), and The Dreaming, are foundational concepts for the treatment. While these concepts are core elements of the project, this book also employs fresh contemporary theory and case studies that present ways to effectively address the deeper psychological origins and presence of trauma in our present-day preschool children, and in traumatized children throughout the world. It gives special attention to the use of therapeutic measures based in psychoanalytic thought and related modes of responding to trauma. Through many moving examples the book unites—through art, stories of The Dreaming, and the ancient gift of listening—a powerful way of approaching present-day work with Aboriginal people and their children. The contributors’ work is at the forefront of field research, clinical work, and theoretical interdisciplinary work. This book is essential to workers and teachers who deal daily with traumatized children in their communities and schools. In the usefulness of its model, the depth of its thinking, and the intensity of its methodology, Transgenerational Trauma and the Aboriginal Preschool Child breaks new ground in the treatment of trauma for people who care for children everywhere.